Towards successful TPACK professional arrangement for in-service teachers - Ansyari, Muhammad Fauzan (Journal of English and Arabic Language Teaching, 2013)
Professional development programmes for technology are essential for teacher capacity to improve students’ achievement. Technological Pedagogical Content Knowledge (TPACK) framework which represents teachers’ knowledge domains, consisting of content, pedagogy, and technology, is used in a number of professional development programmes. This review is aimed at investigating the implementation of in-service teachers’ TPACK professional development arrangements for technology integration using technological pedagogical content knowledge (TPACK) framework. In doing so,this review used five major online databases: ERIC, Web of Science, Scopus, Informaworld, and SpringerLink, with the criteria of studies addressing in-service teachers’ TPACK professional development arrangements for technology integration, except for first aim since it addresses the concept of TPACK; deal with teachers teaching students without disabilities; and must be conducted between 2006 and 2012.In general, the results of this review show three different conceptualisations of TPACK model: initial model of TPACK, ICT-TPACK model, and elaborated TPACK model. Moreover, inquiry learning approach, peer-coaching, authentic learning, problem-based learning, project-based learning, and learning activity typeswere employed in successful TPACK professional development programmes for in-service teachers. In addition, several factors contributing to such successful programmes include engagement, authentic learning experiences, collaboration, supports, curriculum coherency, reflection, feedback, intensive training, and longer time. Finally, teachers were reported having positive experiences with such programmes.